2016
DOI: 10.1093/cercor/bhw184
|View full text |Cite
|
Sign up to set email alerts
|

Words in Context: The Effects of Length, Frequency, and Predictability on Brain Responses During Natural Reading

Abstract: Word length, frequency, and predictability count among the most influential variables during reading. Their effects are well-documented in eye movement studies, but pertinent evidence from neuroimaging primarily stem from single-word presentations. We investigated the effects of these variables during reading of whole sentences with simultaneous eye-tracking and functional magnetic resonance imaging (fixation-related fMRI). Increasing word length was associated with increasing activation in occipital areas lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 125 publications
8
76
1
Order By: Relevance
“…Previous fMRI studies observed word frequency effects in several brain regions including the left inferior frontal and occipito-temporal regions (Chee, Venkatraman, Westphal, & Siong, 2003;Hauk, Davis, & Pulvermüller, 2008;Schuster, Hawelka, Hutzler, Kronbichler, & Richlan, 2016), not in the ATL, which is the region of interest in the current study. In this validation analysis, increasing word frequency was significantly associated with higher activation in the left inferior frontal gyrus and with lower activation in the bilateral occipitaltemporal regions ( Figure S3A and Table S1), but not in the ATL, even at a lenient threshold of voxelwise p < .001, cluster size ≥10 voxels.…”
Section: Validation Analysis: Controlling For the Potential Effect mentioning
confidence: 95%
“…Previous fMRI studies observed word frequency effects in several brain regions including the left inferior frontal and occipito-temporal regions (Chee, Venkatraman, Westphal, & Siong, 2003;Hauk, Davis, & Pulvermüller, 2008;Schuster, Hawelka, Hutzler, Kronbichler, & Richlan, 2016), not in the ATL, which is the region of interest in the current study. In this validation analysis, increasing word frequency was significantly associated with higher activation in the left inferior frontal gyrus and with lower activation in the bilateral occipitaltemporal regions ( Figure S3A and Table S1), but not in the ATL, even at a lenient threshold of voxelwise p < .001, cluster size ≥10 voxels.…”
Section: Validation Analysis: Controlling For the Potential Effect mentioning
confidence: 95%
“…First, robust activations were found in the lingual gyrus and the adjacent cerebellum. Differences in length between sentence and word stimuli can contribute to activity in the lingual gyrus (Schuster, Hawelka, Hutzler, Kronbichler, & Richlan, 2016). Differences in length between sentence and word stimuli can contribute to activity in the lingual gyrus (Schuster, Hawelka, Hutzler, Kronbichler, & Richlan, 2016).…”
Section: Common Neural Circuitry Underlying Tafmentioning
confidence: 99%
“…Phrases that contained adjectives that were followed by a noun remained on the screen until the noun disappeared. This display protocol (as opposed to presenting one word at a time or one sentence at a time) was adopted to approximate the type of encoding that is indicated by eye fixation studies of text reading (Just & Carpenter, 1980;Schuster, Hawelka, Hutzler, Kronbichler & Richlan, 2016). Presentation of a sample sentence: A familia estava feliz (The family was happy).…”
Section: Experimental Paradigmmentioning
confidence: 99%